(untitled) (Economics and region, 2020)
The main goal of the article is to investigate media support of enterprises engaged in foreign economic activity. The article deals with the concept of media literacy as a basis of a media support at enterprises. Media information sources are systematized, and Text-mining is found to be an effective tool for extracting competitive knowledge from media information data. It is substantiated that functioning of a media information system has significant positive effects and shifts not only for an enterprise where the system operates, but for a country as a whole. It is proved that state policy should be guided by the vector of providing media information support to enterprises regarding their foreign economic activity.